2014
DOI: 10.7314/apjcp.2014.15.16.6787
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 (COX-2) in Colorectal Adenocarcinoma: an Immunohistochemical and Histopathological Study

Abstract: Background: The aim of this study was to evaluate cyclooxygenase-2 (COX-2) immunoreactivity in colorectal adenocarcinomas and to find correlations with different pathological features. Materials and Methods: This study included 35 cases of colorectal carcinoma foir which surgical colectomy specimens were collected. Immunohistochemical staining of COX-2 (cyclooxygenase-2) is done by using the Streptavidin-biotin technique. Results: This work reveals that COX-2 is positive in most cases of colorectal carcinoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
5
10
0
Order By: Relevance
“…However, they did not observe any association between clinicopathological parameters and expression of COX-2. The results of the present study are also supported by the observation of Mahmoud et al, (2014), who have found no association between COX-2 expression and the clinicopathological features except for association between COX-2 expression and gender. Contradictory to results of present study, COX-2 expression was significantly linked with the depth of tumor invasion in another study (Lim et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, they did not observe any association between clinicopathological parameters and expression of COX-2. The results of the present study are also supported by the observation of Mahmoud et al, (2014), who have found no association between COX-2 expression and the clinicopathological features except for association between COX-2 expression and gender. Contradictory to results of present study, COX-2 expression was significantly linked with the depth of tumor invasion in another study (Lim et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…It is well documented that COX2 expressions are higher in CRC than those in the paracarcinoma tissues. [ 10 11 ] In this work, we showed that both mRNA and protein levels of COX2 were upregulated in CRC by bioinformatics and immunohistochemistry analysis. In addition, cytoplasmic and cytomembranous COX2 is associated with pathological stage, tumor recurrence, metastasis, and poor patient prognosis, and is an independent prognostic factor in CRC.…”
Section: Discussionmentioning
confidence: 89%
“…With respect to molecular mechanisms of action, mounting data confirm that the inhibition of this process may be a critical event in the development of colonic tumors (3, 24, 29, 30). Cyclooxygenase-2 (COX-2) is an enzyme that converts arachidonic acid (20:4, n−6) to prostaglandin E 2 , and has been reported to be involved in colonic tumor development (31, 32). Studies have shown that prostanglandins produced by COX-2 promote colon cell proliferation and inhibit apoptosis (32).…”
Section: Discussionmentioning
confidence: 99%